Decreased sensitivity of 5-HT(1D) receptors in melancholic depression. - Whale, R; Clifford, E; Bhagwagar, Z; Cowen, P (2001)
BACKGROUND: Brain serotonin (5-HT) function is abnormal in major depression, but the involvement of different 5-HT receptor subtypes has been little studied. The availability of selective ligands now makes it possible to test the sensitivity of 5-HT(1D) receptors in patients with depression. AIMS: The aim of the study was to use the 5-HT(1D) receptor agonist, zolmitriptan, to test the sensitivity of 5-HT(1D) receptors in patients with depression before and after treatment with selective serotonin reuptake inhibitors (SSRIs). METHOD: We measured the growth hormone response to zolmitriptan (5 mg orally) in patients with major depression before and after SSRI treatment. A matched sample of healthy subjects acted as a control group. RESULTS: The growth hormone response to zolmitriptan was blunted in patients with a melancholic depressive syndrome. SSRI treatment produced a marked reduction in zolmitriptan-induced growth hormone release. CONCLUSIONS: Patients with melancholic depression have impaired sensitivity of the post-synaptic 5-HT(1D) receptors that mediate growth hormone release. The reduction in 5-HT(1D) receptor sensitivity following SSRI treatment is probably an adaptive response to increased levels of synaptic 5-HT.